Strategi Komunikasi Digital: Media Sosial Instagram Sebagai Sarana Promosi di MI Unggulan Darul Mujtaba - Salvadora Erik Presica; Ahmad Bukhori (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to identify and analyze effective digital communication strategies through Instagram social media that can be implemented by MI Unggulan Darul Mujtaba as a promotional tool. In the current digital era, social media plays an important role in building an image and attracting public interest in educational institutions. However, the challenge faced is how to optimally utilize Instagram social media to achieve these promotional goals. This research uses descriptive qualitative research with data collection methods in the form of interviews and in-depth observations of research subjects and objects. The research results show that the success of the digital communication strategy at MI Unggulan Darul Mujtaba can be seen from increased visibility, high levels of engagement, positive feedback, and an increase in the number of new student registrations. With a well-planned and implemented strategy, MI Unggulan Darul Mujtaba can make maximum use of Instagram's potential to build a positive image and attract public interest. This research contributes to the development of literature on digital communication and promotional strategies in the era of social media, as well as providing practical guidance for other educational institutions that wish to optimize the use of social media for promotional purposes.